2015
DOI: 10.7314/apjcp.2015.16.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Educational Intervention among Public Health Midwives on Breast Cancer Early Detection in the District of Gampaha, Sri Lanka

Abstract: Background: Breast cancer is the commonest cancer among Sri Lankan females, accounting for 26% of the cancer incidence in women. Early detection of breast cancer is conducted by public health midwives (PHMs) in the Well Woman Clinics. The aim of the present study was to determine the effectiveness of an educational intervention on improving knowledge, attitudes and practices (KAP) on breast cancer screening among PHMs in the district of Gampaha. Materials and Methods: Two Medical Officer of Health (MOH) areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of the seven studies that examined knowledge as the primary outcome, five controlled intervention studies demonstrated improvement in knowledge of health care professionals through video training, presentations, discussions, role‐plays, and learning through the review of academic papers and booklet material . Two quasi‐experimental studies that used audio‐visual educational activities demonstrated significant improvement in knowledge scores for breast cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies that examined knowledge as the primary outcome, five controlled intervention studies demonstrated improvement in knowledge of health care professionals through video training, presentations, discussions, role‐plays, and learning through the review of academic papers and booklet material . Two quasi‐experimental studies that used audio‐visual educational activities demonstrated significant improvement in knowledge scores for breast cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Targeted in-service education referred to essential maternal and newborn health-related skills. Other focus areas included partograph use [88], neonatal care [84], use of alternate birth positions [29] and antenatal care [43], HIV [89], family planning [90], mental health [91], ultrasound [92], patient safety [93], family violence [94], digestion health, nutrition and parenting [95], breast cancer [96], mammography [97], disaster preparedness and management [98], electronic health record system [47] and pharmacovigilance [99]. Targeted in-service education was offered for career pathway development, specifically professional education, academic progress, self-development or professional recognition, or with external incentives such as career paths, policies, workplace or professional organisation.…”
Section: In-service Education or Continuing Professional Developmentmentioning
confidence: 99%
“…But, mammographic facilities are costly and available only at limited places (Vithana et al, 2015). Consequently, the new technology electrical impedance tomography (EIT) which is a relatively new imaging method that has evolved over the past 20 years is recommended (Hope et al, 2004).…”
Section: Electrical Impedance Tomography As a Primary Screening Technmentioning
confidence: 99%